Pelatihan Pengisian SPT Tahunan Orang Pribadi (OP) pada Mahasiswa Prodi Akuntansi Universitas Bumigora - R . Ayu Ida Aryani; Ikang Murapi; Dewa Ayu Oki Astarini; Ni Ketut Sriwinarti; Khairan Marzuki (LPPM Universitas Bumigora, 2022)
The community service program implemented at Bumigora University aims to: carry out training activities with all students of the Accounting study program, in training on Procedures for Filling in Annual Personal Income Tax Return. The service material presented was training on reporting and filling out the Annual Personal Income Tax Return in hall 3 of the Bumigora University building. The method used in this activity namely by giving lectures / giving material followed by discussion and question and answer responsibility between presenters and participants in filling out the Annual Personal Income Tax Return. Training results The completion of the Annual Personal Income Tax Return is expected to make a significant contribution in the form of knowledge and skills that can be used as provisions in readiness to become a skilled workforce in the field of Accounting and Taxation to be able to compete in the world of work.